BARRIERS TO CLOZAPINE USE IN TREATMENT-REFRACTORY POPULATION IN KARACHI, PAKISTAN - Shad, Mujeeb Uddin; Hasan, Shahzain (Journal of Pakistan Psychiatric Society, 2023)
Objective: To investigate the causes accountable for serving as barriers in prescribing clozapine in several outpatient departments in Karachi, Pakistan. Study Desgin: A cross- Sectional Study. Duration and Place od Study: Psychiatrist and residents conducting clinics in karachi, May to July 2022. Method: This study was conducted over three months periods, using a structured questionnaire from 105 physicians with previous formal training in psychiatry. Statistical analysis was done using the Chi-Square test of association. Results: Out of 105 doctors offering psychiatric services at various locations, 70% mentioned that they were uncomfortable prescribing clozapine earlier in the course, with its adverse effects profile being the most popular reason for its avoidance by the patients and/or their families. Clozapine’s availability and its cost were also common barriers to prescribing clozapine. Most doctors agreed that they would have felt more comfortable if they had had some clozapine training and attended clozapine clinics during their training. Conclusion: The anticipation of medication nonadherence and monitoring requirements coupled with overestimating the adverse effect profile stems from inadequate experience with the drug Steps should be taken by the graduate medical education at the training hospitals to organize clozapine clinics and offer clozapine training to promote the use of this effective drug to improve the prognosis and function suffering from this debilitating illness.